High performances niobium oxides based negative electrode for lithium ion batteries - Ji, Qing (2021)
Lithium ion batteries have been widely applied since 1990s due to high energy out-put, stable cyclability, and eco-friendly. While, the fast-growing demands of higher performances from electric vehicles urged the emergence of next generation batteries. Typically, a lithium-ion battery consists of negative/positive electrode, separator and electrolyte. The improved performances of negative electrodes could significantly increase the final energy out-put of the battery. Among the negative electrode materials, niobium oxides (Nb2O5, NbO2 and NbO) exhibit great potential due to high theoretical specific capacity and rapid Li-ion transport. However, intrinsic low electron conductivity leads to large polarization and ion diffusion constraint, which hampers the cycling life of niobium-oxides-based electrodes. This thesis focuses developing new niobium oxides based negative electrode to achieve high performances. Facile method is used for fabricating electrode. Underneath mechanism, i.e. the lithium ion insertion behavior of niobium oxides which driven the higher performance of electrodes is revealed. NbOx nano-particles embedded in carbon matrix are synthesized using dental resin monomer (bisphenol A glycidyl dimethacrylate, Bis-GMA) as solvent and carbon source and niobium ethoxide (NbETO) as the precursor. Thermal polymerization and calcination under Ar/H2 atmosphere at 900 oC are applied, where niobium oxides/carbon nanohybrids are synthesized in a facile scalable way. Note that, with simply controlling the feeding ratio of the resin and Nb precursors, diverse nanohybrids with super-small particles of Nb2O5 (3-10 nm) and nanoparticles of NbO2 (20 nm) are synthesized respectively. Furthermore, carbon structure ranges from compact to mesoporous is observed as well. Thus, high resin content tends to form super-small Nb2O5 particles embedded in dense carbon matrix, while NbO2 nano-particles with mesoporous carbon is induced at low resin content. The mechanism of structure variations with decreasing resin content, including reduction of NbOx, ascending size distribution and meso-pores generation in carbon matrix is revealed. It is revealed that a low Bis-GMA/NbETO mass ratio (from 1:1 to 1:2) enables the conversion of Nb (V) to Nb (IV) due to increased porosity induced by alcoholysis reaction between the NbETO and Bis-GMA. In addition, following electrochemical tests find that, combined with reduced particle size and conductive carbon matrix, all NbOx/Carbon nanohybrids present improved cyclability. Nb2O5/Carbon nanohybrids retain around 90 % capacity after 200 cycles at 0.2 C, and deliver capacity of 225 mA h g-1 after 500 cycles at 1 C rate. Coulombic efficiency of all nanohybrids increases to more than 99 % in 10 cycles. Various experimental and theoretical approaches including solid state nuclear magnetic resonance, ex situ XRD, differential electrochemical mass spectrometry, and density functional theory (DFT) are utilized to understand the fundamental lithiation/delithiation mechanism of the NbO2/carbon nanohybrid. The results suggest that the NbO2/carbon nanohybrid bearing high capacity, long cycle life and low gas-evolution is promising for lithium storage applications. A new carbon-emcoating architecture through single CO2 activation treatment is designed for Nb2O5/Carbon nanohybrid. Triple structure engineering of the carbon-emcoating Nb2O5/Carbon nanohybrid is achieved in terms of porosity, composition, and crystallographic phase. Compared with conventional carbon coating structure, the newly developed both carbon-emcoating Nb2O5/Carbon nanohybrids deliver superior cycling and rate performance.